Interculturality in the Ecumenical School of Religious Sciences. - Méndez Méndez, Jose Mario (2021)
This work analyzes the presence of the intercultural perspective in the curricular instruments produced by the Ecumenical School of Religious Sciences from 1975 to the present. The study focuses on the objectives and objects of study described in the documents addressed. The intercultural is traced in the contextual nature of the educational proposals, in the way in which the study plans take charge of religious and cultural diversity, and in the contributions to overcoming cultural violence.